Finite element analysis of braced excavation in mixed soil - Hagiwara, Tomozumi (Nanyang Technological University, 2022)
Numerous numerical studies have been published for braced excavations in sand or soft/stiff clays individually, but there are limited studies on mixed soils with sand overlying clay or clay overlying sand. This study will investigate the wall lateral deflection and strut forces for an excavation in a sand deposit overlying a soft clay. The Hardening-Soil model was used to model the stress-strain behaviour of the soil. The effects of various parameters, such as the thickness of the sand layer, the soil strength, wall types and width of excavation are analyzed using the plane strain finite element software PLAXIS 2D. The results show that the lateral wall deflection increases with the presence of soft clay. Additionally, the wall deflection increases when the undrained shear strength of the soft clay decreases. Furthermore, the lateral wall deflection decreases with an increase in wall stiffness EI, sand friction angle and decrease in excavation width. However, there seems to be no distinct relationship between the maximum strut force and varying wall types, soil properties and excavation width. For most of the cases considered, Peck’s (1969) Apparent Pressure Diagram (APD) overestimated or underestimated the strut forces.